Correction: Mahmoud et al. Coriander Oil Reverses Dexamethasone-Induced Insulin Resistance in Rats. Antioxidants 2022, 11, 441 - Mona F. Mahmoud; Noura Ali; Islam Mostafa; Rehab A. Hasan; Mansour Sobeh (MDPI AG, 2024)
In the original publication [...]